Enhancing Employee Performance Through Leadership Styles and Supportive Work Environment - Rahmayanti, Risti Sagita; Manafe, Leonard Adrie; Nugroho, Agung Dwi (LPPPIPublishing, 2025)
This study investigates how leadership patterns and workplace conditions affect staff performance at the Surabaya City Statistics Agency. The researchers chose a qualitative approach with a case study design, combining in-depth interviews, direct observation, and review of official agency documents. Field findings reveal that managers at the Surabaya City Statistics Agency employ two main approaches: transactional and transformational leadership. The transactional method tends to emphasise target achievement and efficiency, often resulting in pressure that disrupts employee well-being. In contrast, transformational leadership motivates and empowers staff, with the impact evident in improved performance in the long term. In terms of physical facilities, the office is adequately equipped, but cramped workspaces and a lack of collaborative areas remain challenges. Nevertheless, close interpersonal relationships and an organisational culture that prioritises data accuracy help boost productivity. The interaction between the two leadership styles and working conditions shows that they influence each other, so their contribution to employee performance cannot be separated. Based on these findings, the study recommends that the leadership of the Surabaya City BPS prioritise transformational leadership and improve the work environment to achieve higher work effectiveness.